ARMADA LAUT DAN JEJAK KEJAYAAN KAUM MUSLIMIN MASA KLASIK - irwan supriadin j (FiTUA: Jurnal Studi Islam, 2021)
This article reviews the Muslim naval fleet using a historical approach. The Muslim naval fleet was introduced by Muawiyah bin Abi Sufyan, the Governor of Syam in the era of the caliph Umar bin Khattab. Furthermore, it was developed during the caliphate of Uthman bin Affan and continued by Muslim rulers after the khulafaurrasyidin such as the Umayyad, Abbasid and Fatimid Empires. this is urgen Especially maintaining the integrity of areas controlled by Muslims such as the coasts of Africa and Europe and securing sea trade routes in important cities in the past such as Baghdad, Tunisia and Andalusia. The ability of the naval fleet, which was equipped with the latest weapons in its time, made the Muslim fleets respected by the European and Byzantine fleets, which were known to dominate the seas first.